2016
DOI: 10.1039/c6lc00414h
|View full text |Cite
|
Sign up to set email alerts
|

In-mold patterning and actionable axo-somatic compartmentalization for on-chip neuron culture

Abstract: Oriented neuronal networks with controlled connectivity are required for many applications ranging from studies of neurodegeneration to neuronal computation. To build such networks in vitro, an efficient, directed and long lasting guidance of axons toward their target is a pre-requisite. The best guidance achieved so far, however, relies on confining axons in enclosed microchannels, making them poorly accessible for further investigation. Here we describe a method providing accessible and highly regular arrays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 43 publications
(67 reference statements)
0
24
0
Order By: Relevance
“…In the present study, we developed polydimethylsiloxane (PDMS) microstructured substrates of various topographies using photolithography and molding. Coated PDMS surfaces have been validated for the culture of various cell types [65], including primary neurons [66]. The final culture coverslip is composed of a thin layer of microstructured PDMS strongly attached on a glass coverslip (Fig.1A).…”
Section: Design Of Microstructured Substrates To Study the Migration mentioning
confidence: 99%
“…In the present study, we developed polydimethylsiloxane (PDMS) microstructured substrates of various topographies using photolithography and molding. Coated PDMS surfaces have been validated for the culture of various cell types [65], including primary neurons [66]. The final culture coverslip is composed of a thin layer of microstructured PDMS strongly attached on a glass coverslip (Fig.1A).…”
Section: Design Of Microstructured Substrates To Study the Migration mentioning
confidence: 99%
“…Noteworthy, when using such cotton threads, the device should be thoroughly sterilized with ethanol before use, not to compromise cell viability during the experiments. Building up on previously developed technology making use of removable filaments in a microfluidic device to create hydrogel structures [56,57] we first confined our 3D cell-hydrogel construct using Nylon filaments (VARIVAS Fluoro carbon Super tippet 2XN 0.235-mm diameter, Morris, Saitama, Japan) inserted in 200-µm high guiding channels through vertical inlets and outlets before bonding of the device. However, those large filaments were not deformable enough to bend and conform with the sharp angle existing at the inlets and outlets of the guiding channels, which significantly hampered bonding of the device with the glass slide, which was not the case for smaller height channels (80 µm) and thinner Nylon fibers (95-µm diameter) in the original paper introducing this technique.…”
Section: Design and Fabrication Of The Microfluidic Systemsmentioning
confidence: 99%
“…In recent years, numerous studies have reported the application of compartmentalized microfluidic platforms for neurobiological research 133135 . The ability to observe the different parts of neurons (axons and cell bodies) in compartmentalized microfluidic devices can be useful for studying neurodegenerative diseases.…”
Section: Stem Cells In Microfluidic-based Neural Tissue Engineeringmentioning
confidence: 99%